Identification of Langerhans-like cells in the immunocompetent tissues of channel catfish, Ictalurus punctatus. (November 2016) - Kordon, Adef O.; Scott, Matthew A.; Ibrahim, Iman; Abdelhamed, Hossam; Ahmed, Hamada; Baumgartner, Wes; Karsi, Attila; Pinchuk, Lesya M.
Abstract: Dendritic cells (DCs) are the most powerful antigen presenting cells (APCs) that have a critical role in bridging innate and adaptive immune responses in vertebrates. Dendritic cells have been characterized morphologically and functionally in the teleost fish models such as rainbow trout, salmonids, medaka, and zebrafish. The presence of DCs with remarkable similarities to human Langerhans cells (LCs) has been described in the spleen and anterior kidney of salmonids and rainbow trout. However, there is no evidence of the presence of DCs and their role in channel catfish immunity. In this study, we assessed DC-like cells in the immunocompetent tissues of channel catfish by immunohistochemistry (IHC), flow cytometry and transmission electron microscopy (TEM). We identified Langerin/CD207 + (L/CD207 + ) cells in the channel catfish anterior kidney, spleen and gill by IHC. Moreover, we described the cells that resembled mammal LC DCs containing Birbeck-like (BL) granules in channel catfish spleen, anterior and posterior kidneys and gill by TEM. Our data suggest that cells with DC-like morphology in the immune related organs of catfish may share morphological and functional properties with previously reported DCs in teleost fish and mammals. More detailed knowledge of the phenotype and the function of catfish DCs will not only help gain insight into the evolution of the vertebrate adaptive immune system but will also provide valuable information for development and optimization of immunotherapies and vaccination protocols for aquaculture use. Highlights: Catfish Langerhans -like cells contain Birbeck granules (BG) and Langerin protein. Langerhans-like dendritic cells (DC) were detected in the lymphoid tissues of catfish. Catfish DC were more abundant in anterior kidney compared to the spleen. Langerhans-like DC containing BG were documented in pathogen-free catfish gill.